Increasing Production of Chicken Farms Using Internet of Things Technology - Abd El Halim Smai, Medhat A. Tawfeek (International Journal of Advanced Science and Technology, 2020)
Smart methodology for chicken farms is a new direction for using modern, intelligent tools derived from Internet of Things technology (IoT), in addition to discontinuing use of old tools and equipment. The smart-chicken-farming model requires additional sensors, actuators, and micro controller units. The main issues for normal chicken farms are related to the behaviour and effect of human elements, including neglect and forgetfulness. In this paper, an adaptive chicken-farm approach called smart chicken farms is proposed. Modern IoT tools are utilised for handling and observing the repeated operation.The proposed method handles all therepetitive dailyoperations controlling the degree of chicken growth, such as temperature, light, water, and required food. Two chicken farms ofthe same size are selected for the experiments. One is a normal chicken farm and the other is a smart chicken farm using the proposed approach. These two farms start with the same quantity of chickens. The results confirm that smart chicken farmsare highly efficient according to measures like overall chicken production, the rate of temperature change and depreciation rate.